2015
DOI: 10.1039/c5ra17967j
|View full text |Cite
|
Sign up to set email alerts
|

Improved interfacial charge transfer and visible light activity of reduced graphene oxide–graphitic carbon nitride photocatalysts

Abstract: rGO–gCN composites, which were prepared by the in situ photoreduction of GO using bulk gCN as the photocatalyst, exhibited higher photocatalytic activity than bare gCN due to the improved interface charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 46 publications
(100 reference statements)
4
14
0
Order By: Relevance
“…The stretching modes of v(C-N) heterocycles were observed at 1200 -1700 cm -1 , while the heterocyclic tri-s-triazine (C 6 N 7 ) was found at around 809 cm -1 . Even though the presence of amino groups in the synthesized CN is difficult to be analysed by FTIR spectroscopy, it has been reported by XPS analysis [31]. It was obvious that the Cu(x)/CN composite exhibited almost similar peaks to those of the CN, which indicated that the structure of CN was kept to be almost the same even after addition of copper species on the samples, similar to other reported literatures [24,32].…”
Section: Results and Discussion Characterization Of Cn And Cu(x)/cn Csupporting
confidence: 84%
See 1 more Smart Citation
“…The stretching modes of v(C-N) heterocycles were observed at 1200 -1700 cm -1 , while the heterocyclic tri-s-triazine (C 6 N 7 ) was found at around 809 cm -1 . Even though the presence of amino groups in the synthesized CN is difficult to be analysed by FTIR spectroscopy, it has been reported by XPS analysis [31]. It was obvious that the Cu(x)/CN composite exhibited almost similar peaks to those of the CN, which indicated that the structure of CN was kept to be almost the same even after addition of copper species on the samples, similar to other reported literatures [24,32].…”
Section: Results and Discussion Characterization Of Cn And Cu(x)/cn Csupporting
confidence: 84%
“…Figure 2. The CN showed vibration bands at around 3300 -3400 cm -1 that can be attributed to the overlapping bands of primary and secondary amine, v(N-H) and v(O-H) groups [21][22][23][24][31][32][33][34][35]. The stretching modes of v(C-N) heterocycles were observed at 1200 -1700 cm -1 , while the heterocyclic tri-s-triazine (C 6 N 7 ) was found at around 809 cm -1 .…”
Section: Results and Discussion Characterization Of Cn And Cu(x)/cn Cmentioning
confidence: 97%
“…However, a high increase to 1.00% rGO content led to a decrease in the photocatalytic activity which may be justified with the decrease of available CN catalyst surface, which seems to be responsible for the direct oxidation of BA into BAL. A similar optimal amount of rGO (i.e 0.10 wt.%) in the rGO/g-C 3 N 4 photocatalyst has been already reported for the degradation of phenol under visible light irradiation; [34] the higher performance of this composite in comparison to bare g-C 3 N 4 was attributed to the suppressed electron hole recombination and also to the improvement of the interface charge transfer. [34]…”
Section: Materials Characterizationsupporting
confidence: 73%
“…A similar optimal amount of rGO (i.e 0.10 wt.%) in the rGO/g-C 3 N 4 photocatalyst has been already reported for the degradation of phenol under visible light irradiation; [34] the higher performance of this composite in comparison to bare g-C 3 N 4 was attributed to the suppressed electron hole recombination and also to the improvement of the interface charge transfer. [34]…”
Section: Materials Characterizationsupporting
confidence: 73%
“…The H 2 production rate of the graphene/g-C 3 N 4 composite is 451 µmol¨h´1¨g´1, 3.07 times more than pure g-C 3 N 4 . Toing's group [120] employed a photocatalytic reduction method to produce RGO/g-C 3 N 4 photocatalysts and evaluated its photocatalytic performance by degradation of phenol under visible light irradiation. They suggested that due to the presence of an aromatic network in both g-C 3 N 4 and RGO, the RGO can interact with g-C 3 N 4 via π-π stacking, which can promote the electron-hole separation and improve the interfacial charge transfer.…”
Section: D/2dmentioning
confidence: 99%